Advanced Computer Architecture 10th Annual Conference, ACA 2014, Shenyang, China, August 23-24, 2014. Proceedings - Wu, Junjie; Chen, Haibo; Wang, Xingwei (Communications in Computer and Information Science, 2014)
This book constitutes the refereed proceedings of the 10th Annual Conference on Advanced Computer Architecture, ACA 2014, held in Shenyang, China, in August 2014. The 19 revised full papers presented were carefully reviewed and selected from 115 submissions. The papers are organized in topical sections on processors and circuits; high performance computing; GPUs and accelerators; cloud and data centers; energy and reliability; intelligence computing and mobile computing.